Utilidade do Relato Financeiro para a Tomada de Decisão Interna no Ensino Superior Público Português - Laureano, Raul M. S.; Jesus, M.; Estrada, F. (XXIV Jornadas Luso Espanholas de Gestão Científica, 2014)
In the last decades financial information disclosed by Governmental Accounting, besides control finalities, raised new purposes to help decision-makers in their decisions. In Portugal the Char of Accounts for Portuguese public education sector (POC-Educação) supports these new purposes, which main goals is to assist the internal decision-makers with useful financial. This study aims to investigate the needs for financial and economic information through the internal decision-makers opinions, evaluating also the usefulness of POC-Educação financial statements for decision-making. Using a survey applied to the internal decision-makers of the public higher education institutions we obtained findings that allow concluding that users feel a high need for the information disclosed by POC-Educação and consider such information useful to support their decisions. We also conclude that the internal users consider the financial reporting established by POC-Educação is overall suitable to support their decision making.